PREDICTION OF MECHANICAL PROPERTIES OF COCRYSTAL KETOCONAZOLE WITH ADIPIC ACID - Indar I (JURNAL FARMASI GALENIKA, 2016)
Most pharmaceutical dosage form contain pharmaceutical active ingredients (APIs) in the form of crystals. In the process of drug development, one of the early decisions that should be made is to determine which form or Polymorph crystals to be used. Deformation characteristics of APIs determines the success of pharmaceutical preparations production processes including tabletation, if the BAF is elastic so the resulting tablets will experience capping or lamination. This study aims to predict the mechanical characteristics of API with analyzing crystals by using a software Mercury 3.3. Ketoconazole (KTZ) and cocrystal ketoconazole with adipic acid (KTZAD) is used as a model and obtained from crystallography Open Database, then performed an analysis of crystal packing motifs, three-dimensional hydrogen bonding and simulate X-ray diffraction pattern for a single crystal ray powder. Based on the analysis, KTZ have a three-dimensional pattern of hydrogen bonds so that the crystal packing does not have a sliding plane (slip plane) which causes the PCT form I have a poor plasticity properties. In cocrystal KTZ-AD can be seen that the hydrogen bonds in the crystal packing has a flat 2-dimensional pattern. This pattern causes the crystal from cocrystal KTZ-AD is to occur plastic deformation.